USING DIGITAL ECONOMY IN COLLECTION AND DISBURSEMENT OF ZAKAH PROCEEDS IN NIGERIA - Haruna Dahiru; Raudatu Inuwa (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
Islam has laid down certain principles and limits for the economic activity of man so that the entire pattern of production, exchange and distribution of wealth shall be in conformity with the laid principles of Maqasidi-Shar’iah. Zakah is one of the medium through which wealth is distributed among the less privilege members of the society. Its’ collection and disbursement have played major role in mitigating the economic hardship among the beneficiaries. In the past, collection and disbursement of Zakat were done through traditional method of face to face. Nowadays the digital technology provided very potential windows to enhance the collection and disbursement of Zakah. Hence, the dire need to harness the digital technology in reaching out to beneficiaries of zakah. This paper therefore examines the potentiality of using the principles of digital economy in collection and disbursement of Zakah in Nigeria. The data collection involves the use of primary and secondary sources. The findings show that digital economy proves effective means in the collection and disbursement of Zakah. The paper recommends the adoption of digital technology by the various Zakah collectors in the collection and disbursement of Zakah proceeds. The paper concludes that adoption of digital economy will go a long way in addressing the problem of unequal distribution among the beneficiaries of zakah in Nigeria and elsewhere in the globe.